Modeling Personas for Older Adults with Heart Failure. (September 2018) - Holden, Richard J.; Joshi, Pushkar; Rao, Kartik; Varrier, Anagha; Daley, Carly N.; Bolchini, Davide; Blackburn, Jessica; Toscos, Tammy; Wagner, Shauna; Martin, Elizabeth; Miller, Amy; Mirro, Michael J.
In the early stages of the design process, designers often benefit from the use of personas, or archetypes of target users presented in a vivid way to highlight design-relevant characteristics. In the growing efforts to create health information technology (HIT) for older adults, empirically derived personas could help orchestrate more user-centered design activities. However, there is a lack of ready-to-use personas for older adult HIT users and more so for those designing in specific domains such as heart failure self-care. This paper presents personas of older adults derived from qualitative analysis of interviews with 24 older patients with heart failure. Analyses unearthed key dimensions distinguishing patients based on their dispositions towards the self-management of their chronic condition, including locus of control, relationship with the health/support system, information needs, and activities of self-care . Two personas are presented: Direction Follower and Researcher, with subtypes for the latter codified as Investigator and Explorer . Our work contributes to future design of systems including HIT to support chronically ill older adults.